Association between physical activity and body fat percentage, with adjustment for BMI: a large cross-sectional analysis of UK Biobank. Issue 3 (24th March 2017) - Bradbury, Kathryn E; Guo, Wenji; Cairns, Benjamin J; Armstrong, Miranda E G; Key, Timothy J
Abstract : Objectives: The objective of this study was to examine if, in the general population, physically active adults have less body fat after taking body mass index (BMI) into account. Design: A cross-sectional analysis of participants recruited into UK Biobank in 2006–2010. Setting: UK Biobank assessment centres throughout the UK. Participants: 119 230 men and 140 578 women aged 40–69 years, with complete physical activity information, and without a self-reported long-term illness, disability or infirmity. Exposures: Physical activity measured as excess metabolic equivalent (MET)-hours per week, estimated from a combination of walking, and moderate and vigorous physical activity. BMI from measured height and weight. Main outcome measure: Body fat percentage estimated from bioimpedance. Results: BMI and body fat percentage were highly correlated (r=0.85 in women; r=0.79 in men), and both were inversely associated with physical activity. Compared with <5 excess MET-hours/week at baseline, ≥100 excess MET-hours/week were associated with a 1.1 kg/m 2 lower BMI (27.1 vs 28.2 kg/m 2 ) and 2.8 percentage points lower body fat (23.4% vs 26.3%) in men, and 2.2 kg/m 2 lower BMI (25.6 vs 27.7 kg/m 2 ) and 4.0 percentage points lower body fat (33.9% vs 37.9%) in women. For a given BMI, greater physical activity was associated with lower average body fat percentage (for a BMI of 22.5–24.99 kg/m 2 : 2.0 (95% CI 1.8 to 2.2), percentage points lower body fat in men and 1.8 (95% CI 1.6 to 2.0) percentage points lower body fat in women, comparing ≥100 excess MET-hours per week with <5 excess MET-hours/week). Conclusions: In this sample of middle-aged adults, drawn from the general population, physical activity was inversely associated with BMI and body fat percentage. For people with the same BMI, those who were more active had a lower body fat percentage.